Innovation in Ornamental Plant Care Systems Based on the Internet of Things (IoT) Using Arduino Leonardo - Supriyanto, Supriyanto; Widiana, Siska Ayu (STMIK Widya Cipta Dharma, 2025)
Anthurium ornamental plants are known for their high aesthetic and economic value, requiring optimal care, particularly in terms of watering, temperature, and soil moisture. However, in practice, the watering process is still mostly done manually and often fails to meet the actual needs of the plants, potentially causing damage or even plant death. Flower Shop